Influence of High Sr2+ Substitution on the Structure and Photocatalytic Activity of Ba1‑XSrxTio3 for Dye Degradation - Dianisa Khoirum Sandi; Trya Andini; Fahru Nurosyid; Yofentina Iriani (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2025)
Barium strontium titanate or BST (Ba1-xSrxTiO3) photocatalysts with distinct Sr substitutions (x = 0.5, 0.6, 0.7, and 0.8) were fabricated using the co-precipitation technique. This study aimed to investigate the influence of the high Sr2+ contents on the structural property and photocatalytic activity to identify the optimal composition. X-ray diffraction (XRD analysis) confirmed cubic BST formation at all Sr concentrations and reduced lattice constants with increasing Sr²⁺ contents. Fourier transform infra-red (FTIR) investigation also validated the formation of the prepared BST with different Sr contents. The photocatalytic activity of the BST photocatalysts was evaluated by the degradation of methylene blue (MB) under UV light irradiation. Notably, the photocatalytic efficiency improved at x=0.5 to x=0.7, attributed to enhanced lattice distortion induced by Sr substitution. However, a further increase of x = 0.8 resulted in reduced photocatalytic activity, likely due to the formation of a more symmetric structure and reduced crystal distortion. Ba₀.₃Sr₀.₇TiO₃ exhibited the highest degradation rate (41%) among all samples tested. The results suggest that the high Sr level critically affects the structural properties and photocatalytic efficiency of BST and underline x = 0.7 as the optimal composition for photocatalytic applications.